Investigation on the sound transmission loss of door sealing system using hybrid FE-SEA method - Azahari, Norzailan (2021)
Vehicle door seals which are located around the car doors play a major role in determining the isolation of the passenger cabin from wind noise and water. The door seals are made from foamed rubber materials so that they can deform into different mating surfaces. As the vehicle is driven at high speeds, turbulence noise from the door seal becomes apparent and the wind noise becomes the primary noise generated into the vehicle interior through the slits or channels on the automotive door surface. The quality of the seals then determines the contribution of the noise level in the cabin. Despite various studies conducted on sound transmission loss (STL) of the door sealing system, the study on modelling the STL using three-dimensional (3D) model is still not well established, especially for a double-seal type. Modelling accurate transmission loss of the seal is still a challenging task and thus this becomes the main objective of this study. The method employs the 3D hybrid Finite Element and Statistical Energy Analysis (FE-SEA) to model the double-seal system and the air channel around the seal using VA-One software. The hybrid model was validated using experimental data from measurement in a diffuse field environment. The result reveals a fairly good agreement between the simulation and experiment with variability of 3 - 10 dB above 1 kHz. The parametric study is then conducted to observe the effect of the thickness, type of material, density, elastic modulus, damping and the cavity size between the frame and door seal on the STL. Especially for the latter, it is revealed that by additional of 2 mm spacing between both seals, the STL can be improved by almost 10 dB above 2 kHz. The comparison of single and double-seal shows that double-seal has significantly greater STL compared to the single seal by 10 - 30 dB at the mass law region above 1 kHz.